Characterization of Soluble Thrombomodulin Fragments in Human Urine - Nakano, Masahiko; Furutani, Masayuki; Hiraishi, Sayuri; Ishii, Hidemi (Thrombosis and Haemostasis, 1998)
The soluble thrombomodulin (TM) subspecies in human urine detected by polyclonal anti-human TM IgG were isolated and characterized. 105, 85, 80, 56, 33, 31 and 28 kDa subspecies under reducing conditions was comparable to 78, 66, 56, 200, 52, 30 and 25 kDa under non-reducing conditions, respectively, in the two-dimensional electrophoresis. Each subspecies under non-reducing conditions, except the 200 and 52 kDa molecules, was constituted of single subspecies, whereas the 200 and 52 kDa molecules were constituted of the tetramer of the 56 kDa subspecies of reducing conditions and a dimer of the 33 kDa subspecies, respectively. NH2-terminal amino acid sequences of the 105, 85 and 80 kDa subspecies maintained Ala1-Pro2-Ala3- of intact human TM, however, 56, 33, 31 and 28 kDa subspecies started from Glu137-Gln138-, Gln214-Gly215-, Ser228-Val229- and Ala240-Ile241-, respectively. All subspecies obtained under non-reducing conditions exhibited cofactor activity for thrombin-dependent protein C activation ranging from 58 to 162 pmol APC/min/nmol TM at 0.4 mM Ca2+ indicating that all of the subspecies maintained the fourth to sixth repeat of epidermal growth factor-like structure of intact TM. 85, 80, 56, 33, 31 and 28 kDa subspecies were suggested to lack both chondroitin sulfate glycosaminoglycan (CSGAG), transmembrane and cytoplasmic domains of intact TM, while 105 kDa subspecies lack only CSGAG from the results of kinetic properties and the interaction with phospholipid vesicles composed from phosphatidylcholine and phosphatidylethanolamine.